2021
DOI: 10.3390/cancers13215571
|View full text |Cite
|
Sign up to set email alerts
|

Dual Hyaluronic Acid and Folic Acid Targeting pH-Sensitive Multifunctional 2DG@DCA@MgO-Nano-Core–Shell-Radiosensitizer for Breast Cancer Therapy

Abstract: Globally, breast cancer (BC) poses a serious public health risk. The disease exhibits a complex heterogeneous etiology and is associated with a glycolytic and oxidative phosphorylation (OXPHOS) metabolic reprogramming phenotype, which fuels proliferation and progression. Due to the late manifestation of symptoms, rigorous treatment regimens are required following diagnosis. Existing treatments are limited by a lack of specificity, systemic toxicity, temporary remission, and radio-resistance in BC. In this stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
1
7
0
Order By: Relevance
“…60,61 Besides, DCApromoting oxidative phosphorylation can reduce the promoting effect of anaerobic glycolysis on VEGF mRNA expression, thereby reducing the risk of angiogenesis. 62,63 In this work, the H 2 O 2 and VEGF changes during DCA treatment were consistent with the research results. Moreover, at low DCA incubation concentrations (2 mg/mL), the generated ROS level was lower than the tolerance threshold of tumor cells, resulting in fewer dead cells.…”
Section: Stability Andsupporting
confidence: 91%
See 1 more Smart Citation
“…60,61 Besides, DCApromoting oxidative phosphorylation can reduce the promoting effect of anaerobic glycolysis on VEGF mRNA expression, thereby reducing the risk of angiogenesis. 62,63 In this work, the H 2 O 2 and VEGF changes during DCA treatment were consistent with the research results. Moreover, at low DCA incubation concentrations (2 mg/mL), the generated ROS level was lower than the tolerance threshold of tumor cells, resulting in fewer dead cells.…”
Section: Stability Andsupporting
confidence: 91%
“…The related mechanism studies have shown that DCA activates the mitochondrial enzyme pyruvate dehydrogenase (PDH), a gate-keeping mitochondrial enzyme, by inhibiting the pyruvate dehydrogenase kinase (PDK) activity, thus gradually shifting the tumor metabolic pattern from glycolysis to mitochondrial oxidative phosphorylation, which promotes a massive increase of ROS including H 2 O 2 to lead to cytotoxicity. ,, In hypoxia, DCA enhances cytotoxicity by further inhibiting glycolysis and amplifying oxidative phosphorylation to promote ROS expansion. , Besides, DCA-promoting oxidative phosphorylation can reduce the promoting effect of anaerobic glycolysis on VEGF mRNA expression, thereby reducing the risk of angiogenesis. , In this work, the H 2 O 2 and VEGF changes during DCA treatment were consistent with the research results. Moreover, at low DCA incubation concentrations (2 mg/mL), the generated ROS level was lower than the tolerance threshold of tumor cells, resulting in fewer dead cells.…”
Section: Resultsmentioning
confidence: 99%
“…The findings of this study showed that PPE treatment of HepG2 cells considerably slowed the proliferation of malignant cells, and that PPE therapy combined with ɣ-irradiation had a synergistic impact. The PPE administration period relative to RT was significant in determining effects, according to radio-modifying implications of PPE in liver cancer cells; reinforcement is often stronger after exposure for 24 hours prior to R. The 6 Gy-R was chosen for additional research since Askar et al 53 found that most of the stimulated damage response systems operate efficiently for a few hours after RT.…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the combination of DCA and 2DG could act as a dual inhibitor of aerobic glycolysis. Given this, a dual-targeted pH-sensitive multifunctional nanoplatform 2DG@DCA@MgO was developed . It is important to note that the MgO core also enhanced the potency of 2DG and DCA.…”
Section: Nanodelivery Systems Based On Glucose Metabolism Reprogrammi...mentioning
confidence: 99%